2017
DOI: 10.1007/s10787-017-0369-5
|View full text |Cite
|
Sign up to set email alerts
|

Alendronate treatment induces IL-1B expression and apoptosis in glioblastoma cell line

Abstract: Alendronate (ALD), one among the nitrogen-containing bisphosphonates (NBPs), is currently used for the treatment of many pathological conditions. Unfortunately, although generally tolerated, NBPs treatment has been associated with central nervous system (CNS) adverse outcomes, such as amnesia, hallucinations and visual disturbances. So, we analyzed the effect of ALD treatment in glial cells, the main sources of cholesterol for neurons and principal cells involved in the immunological defense of the brain. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…TNF-α and IFN-γ have been shown to synergistically induce apoptosis via the induction of nitric oxide [ 33 ]. Also, IL-1β can induce cell death by apoptosis [ 34 ]. Generally, anti-apoptotic properties that lead to a great neuron survival involve reduction in apoptosis mediators as well as oxidative substances, such as superoxide dismutase and hydrogen peroxide.…”
Section: Resultsmentioning
confidence: 99%
“…TNF-α and IFN-γ have been shown to synergistically induce apoptosis via the induction of nitric oxide [ 33 ]. Also, IL-1β can induce cell death by apoptosis [ 34 ]. Generally, anti-apoptotic properties that lead to a great neuron survival involve reduction in apoptosis mediators as well as oxidative substances, such as superoxide dismutase and hydrogen peroxide.…”
Section: Resultsmentioning
confidence: 99%
“…IL-1β is a crucial gene that helps to regulate inflammatory response, [44] and is involved in cell proliferation, differentiation, and apoptosis. [45] Similarly, TNF-α is an inflammatory cytokine that arises during acute inflammation. It can lead to cell death, but it is also an important factor in fighting cancer or infections.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that NLRP3 inflammasome are closely related to the innate immune response of the body. Multiple pathogen-associated molecular patterns and risk-related molecular patterns can activate inflammasome, cause the production of pro-inflammatory cytokines such as IL-1β and provoke apoptosis [16,17]. Emerging studies have shown that NLRP3 inflammasome plays an important role in the development of CI-AKI in vivo and in vitro studies, and mediates downstream apoptosis and inflammatory responses [18,19].It is well known that the mechanism of CI-AKI is closely related to oxidative stress, apoptosis and inflammatory response [20,21].…”
Section: Sift Desk Discussionmentioning
confidence: 99%